2002
DOI: 10.1002/jmv.2202
|View full text |Cite
|
Sign up to set email alerts
|

Mother‐to‐infant transmission of hepatitis C virus: Rate of infection and assessment of viral load and IgM anti‐HCV as risk factors*

Abstract: One hundred twenty-six mother-infant couples were studied and 105 exposed babies were monitored for at least 12 months to define the risk of mother-to-infant HCV transmission. Infection occurred in 5 out of 76 infants (6.6%) born to 69 viraemic mothers and in none of 29 born to 26 non-viraemic mothers. Only one child was HCV RNA positive one month after birth, while the remaining children became positive at the 3rd to 4th month. HCV genotypes of the babies matched those of their mothers. No difference was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(64 citation statements)
references
References 37 publications
5
55
0
4
Order By: Relevance
“…Since viral screening began to be used routinely in blood donors, vertical transmission became the main cause of hepatitis C in children. Vertical transmission occurs in approximately 5% of HIV-negative mothers and in up to 25% of mothers co-infected with HIV [14] . asymptomatic relatives.…”
Section: Viral Hepatitismentioning
confidence: 99%
“…Since viral screening began to be used routinely in blood donors, vertical transmission became the main cause of hepatitis C in children. Vertical transmission occurs in approximately 5% of HIV-negative mothers and in up to 25% of mothers co-infected with HIV [14] . asymptomatic relatives.…”
Section: Viral Hepatitismentioning
confidence: 99%
“…This seems to be related to the fluctuation of HCV viral loads above and below the sensitivity level of the test, or resulting from the use of testing methods that are not sensitive enough to detect low levels of HCV RNA. Depending on the load of the virus, the risk of transmission from positive HCV RNA mothers may become greater (13), although a specific cut-off value predicting or excluding transmission, has yet to be defined (14,15). HCV and HIV coinfection in mothers can increase the risk of transmission substantially (16).…”
Section: Ziyaeyan M Et Al Hcv Transmission To the Orphan Newbornsmentioning
confidence: 99%
“…Mechanisms leading to perinatal HCV transmission are currently not well understood. Likely risk factors include perinatal practices (fetal scalp monitoring and caesarean‐section delivery), extended exposure to maternal blood, high levels of HCV viremia during pregnancy, and co‐infection with human immunodeficiency virus (HIV) 15, 16, 17, 18, 19. Although some studies have challenged several of these assumptions,20, 21 a recent meta‐analysis concluded that maternal HIV co‐infection is the most important determinant of the risk of perinatal transmission 15…”
Section: Epidemiologymentioning
confidence: 99%